Prevalence and epidemiology of Mycoplasma genitalium and the absence of macrolide resistance in M. genitalium among pregnant women attending antenatal care in Zambia - Schröder, Daniel; Sorano, Sumire; Shipitsyna, Elena; Chaponda, Enesia Banda; Golparian, Daniel; Chikwanda, Ephraim; Mwewa, Vivian; Mulenga, Joyce M.; Chaponda, Mike; Smith, Chris; Mitsuaki, Matsui; Mirandola, Massimo; et al. (Frontiers in Public Health, 2025)
IntroductionMycoplasma genitalium (MG) is a sexually transmitted bacterium of public health importance, associated with genitourinary disorders, and adverse reproductive and perinatal outcomes. Global data on MG prevalence and antimicrobial resistance (AMR) are primarily available from high-income countries, whereas there is a dearth of information from resource-constrained settings including sub-Saharan Africa. Furthermore, international data on MG rates and AMR in the antenatal population are scarce. Understanding MG prevalence and AMR patterns is crucial for developing effective public health strategies and treatment guidelines. The aim of this study was to investigate the prevalence and epidemiology of MG and the presence of macrolide resistance-associated mutations (MRAMs) among pregnant women attending antenatal care facilities in Zambia.MethodsA cross-sectional study was conducted at four antenatal care facilities in Nchelenge, Zambia, among 1,021 pregnant women. Vaginal swabs were collected and tested using the Aptima Mycoplasma genitalium assay, Aptima Combo 2 assay and Aptima Trichomonas vaginalis assay on the Panther System (Hologic). MG-positive samples were further analyzed for MRAMs using the ResistancePlus™ MG assay (SpeeDx).ResultsThe prevalence of MG was 12.6% (127 of 1,005 valid samples) among the pregnant women. Only 12 MG-positive women (9.4%) had symptoms of a genitourinary infection, which was similar to the frequency of genitourinary symptoms among MG-negative women (6.1%). The rates of Chlamydia trachomatis, Neisseria gonorrhoeae, T. vaginalis, and HIV seropositivity were 7.4, 8.3, 23.0, and 8.6%, respectively. MG infection was significantly associated with the presence of all other tested sexually transmitted infections and HIV seropositivity: the detection rates of C. trachomatis, N. gonorrhoeae, T. vaginalis, and HIV seropositivity were significantly higher in MG-positive than in MG-negative women (15.1% vs. 6.2, 15.0% vs. 7.5, 32.3% vs. 22.0, and 14.3% vs. 7.5%, respectively). The ResistancePlus™ MG assay detected MG in 66.1% (84/127) of samples positive by the Aptima M. genitalium assay, however, no MRAMs were detected in the 23S rRNA gene for any of these 84 samples.DiscussionThis study emphasizes the high prevalence of MG among pregnant women in Zambia, but also lack of MRAMs in MG. These findings suggest that azithromycin remains an efficacious treatment option for MG in this population. Nevertheless, continuous surveillance and judicious macrolide use to maintain treatment efficacy are imperative. Further research and sustained monitoring of MG are essential to inform public health strategies and clinical guidelines in Zambia and similar settings worldwide.